(untitled) (Dermatology Reports, 2024)
The text discusses the role of general practitioners (GPs) in the prevention and early diagnosis of melanoma, a type of skin cancer. It highlights the need for GPs to be able to recognize suspicious skin lesions and refer patients to specialist dermatology centers. However, many GPs lack comprehensive training in diagnosing melanoma. The text mentions that various training courses have been conducted for GPs, but their impact on clinical practice has been limited. The MelaMEd Programme is an e-learning course developed by the Italian Melanoma Intergroup (IMI). The programme aims to provide GPs with comprehensive knowledge of melanoma prevention, diagnosis, and treatment. It includes an e-learning section, and a dedicated platform called MelaMEd platform, which offers a multimedia atlas of melanoma. The objective of the study is to evaluate the impact of the MelaMEd programme on GPs’ diagnostic accuracy, knowledge of melanoma, and management of suspicious lesions. The methodology involves administering pre-training and post-training questionnaires to participants, assessing their diagnostic skills and evaluating the training course’s effectiveness. The study aims to demonstrate the effectiveness of the MelaMEd programme in improving GPs’ ability to recognize and manage melanoma. It also seeks to identify areas for improvement and recommend interventions to enhance diagnostic accuracy. The results will be analyzed statistically using descriptive, univariate, and multivariate analysed methods.